Thermal and spectral response characterisation of solid samples using photothermal technique - Ling, Yoke Ting (2001)
In this study, a polyvinylidene difluoride (PVDF) film was used as a pyroelectric detector in the lateral distance scanning technique to determine the thermal diffusivity of solid samples. The samples of interest were aluminuim, copper and spray paint. The values were very close to the values obtained by previous works. Next, the open photoacoustic cell (Ope) technique was used for measuring thermal diffusivity of ferrite samples. The values obtained were in the range of 0.3 cm2s- 1 to 0.5 cm2s-1. EDAX analysis proved that zinc loss happened when the sample was sintered at high temperature and the loss was accompanied by sample shrinkage and density increment. Thus, the thermal diffusivity value increased with the amount of zinc loss during the sintering process. A photopyroelectric spectroscopic (P2ES) technique was developed and applied to solid samples such as poly-methyl methacrylate doped with methylene red (PMMAMR), poly-methylmethacrylate doped with Rhodamine B (PMMA-RB) and plant leaves to see the absorption and transmission spectrum range of samples. The spectra obtained showed that they were of transmission type as predicted by Mandelis and Zver. The sample condition, that was fls< Ls, Ip>Ls, in obtaining the spectrum agreed with Mandelis and Zver's prediction. The trend of optical transmission spectrum fm doped PMMA-MR suggests that it could be used as a cut off filter in the range of 525nm and below to 400nm. The spectrum of PMMA-RB showed an absorption range between 500 to 550nm and a highly transmitted region above 600nm. The P2E spectra of leaf obtained were in line to the leaf absorption spectrum obtained by Lima et a1. A young leaf has a higher signal compared to a mature leaf because it is thinner and thus the optical absorption length is longer than the mature leaf. At the saturated transmission spectral region, the logarithmic signal of all these samples was found decreasing linearly with square root of chopping frequency, agreeing to Rosencwaig and Gersho's prediction. The spectrum of ferrite samples showed that the spectrum was similar to that of light source because its optical length, Ip, was still small compared to sample thickness, Ls.